Topical Administration of a Soluble TNF Inhibitor Reduces Infarct Volume After Focal Cerebral Ischemia in Mice - Yli-Karjanmaa, Minna; Clausen, Bettina Hjelm; Degn, Matilda; Novrup, Hans Gram; Ellman, Ditte Gry; Toft-Jensen, Peter; Szymkowski, David E.; Stensballe, Allan; Meyer, Morten; Brambilla, Roberta; Lambertsen, Kate Lykke (Frontiers in Neuroscience, 2019)
Background: Tumor necrosis factor, which exists both as a soluble (solTNF) and a transmembrane (tmTNF) protein, plays an important role in post-stroke inflammation. The objective of the present study was to test the effect of topical versus intracerebroventricular administration of XPro1595 (a solTNF inhibitor) and etanercept (a solTNF and tmTNF inhibitor) compared to saline on output measures such as infarct volume and post-stroke inflammation in mice. Methods: Adult male C57BL/6 mice were treated topically (2.5 mg/ml/1µl/hr for 3 consecutive days) or intracerebroventricularly (1.25 mg/kg/0.5 ml, once) with saline, XPro1595, or etanercept immediately after permanent middle cerebral artery occlusion (pMCAO). Mice were allowed to survive 1 or 3 days. Infarct volume, microglial and leukocyte profiles, and inflammatory markers were evaluated. Results: We found that topical, and not intracerebroventricular, administration of XPro1595 reduced infarct volume at both 1 day and 3 days after pMCAO. Etanercept showed no effect. We observed no changes in microglial or leukocyte populations. XPro1595 increased gene expression of P2ry12 at 1 day and Trem2 at 1 and 3 days, while decreasing Cx3cr1 expression at 1 and 3 days after pMCAO, suggesting a change in microglial activation towards a phagocytic phenotype. Conclusions: Our data demonstrate that topical administration of XPro1595 for three consecutive days decreases infarct volumes after ischemic stroke, while modifying microglial activation and the inflammatory response post-stroke. This suggests that inhibitors of solTNF hold great promise for future neuroprotective treatment in ischemic stroke.